An approximation to the definition of existential analysis in the Logotherapy of Viktor Frankl - Ramos Franco, Luis Alonso (2015)
The present essay is intended to initiate a preliminary exploration of the meaning of “existential analysis” in the Logotherapy of Viktor Frankl, conceptualizing specifically the notions of “analysis” and “existential” as well as the anthropological foundation that this type of therapeutic approach claims. It will be shown that the term “existential analysis” seeks to evoke both the foundation of a psychotherapy as well as the foundation of a human movement that becomes conscious in order to find spiritual meaning in the human concreteness, and that it finally stabilizes in the form of an unconscious habit.